Legal Protection of Health Center Heads the Bottom has No SIP - Br.Sembiring, Tamaulina; Suryati, Dewi (Formosa Journal of Science and Technology, 2024)
Health workers who provide health services must have a Practice License issued by the government in accordance with applicable regulations. The purpose of this Practice Permit (SIP) is to protect both the public and health workers themselves, in terms of health practices that can have a negative impact, both physically, mentally and on the lives of patients. This research aims to identify the legal protection given to heads of community health centers when their subordinates do not have an SIP. The method used in this research is qualitative research with a case study approach. The results show that the head of the community health center can be involved in legal problems if employees at the community health center do not have a practice permit, in accordance with Law Number 17 of 2023 concerning Health. In fact, some health workers do not have a license to practice because they have not received a recommendation from a professional organization, have not passed a competency test, or do not have a valid Registration Certificate (STR). Therefore, it is recommended that the head of the community health center check the existence of a SIP for every health worker working at the health center, and ensure that they understand and comply with the legal regulations governing health workers' practice permits.